Exploring probiotic potential and antimicrobial properties of lactic acid bacteria from cow's milk - Almeida, Jaqueline Milagres de; Maffei, Juliana Takahashi; Gebara, Clarice; Minafra, Cintia; Toledo-Silva, Bruno; Gonçalves, Mônica Correia; Langoni, Helio [UNESP]; Neto, André Thaler; Souza, Fernando Nogueira; Silva, Nathalia Cristina Cirone (Elsevier, 2024)
One of the most important foods in the world is milk, due to its nutrients and composition. Milk also contains lactic acid bacteria (LABs), which can produce antimicrobial compounds and organic acids; an essential factor in developing different methods to control other bacteria. Another critical factor is that several species of LABs are considered potential probiotics, offering several health benefits. This study aimed to isolate, identify LABs, characterize the antimicrobial susceptibility profile, and evaluate the inhibition potential against Staphylococcus aureus (ATCC 25923), Listeria monocytogenes (ATCC 7644), Escherichia coli (ATCC 25922) and Salmonella Typhimurium (ATCC 14028); as well as verifying the acidification capacity, survival of simulated in vitro gastrointestinal conditions and identification of virulence genes and bacteriocin-producing genes. The study was carried out with LABs previously isolated from milk of cows with clinical mastitis, low and high (Somatic Cells Count) in herds from all regions of Brazil (South, Southeast, Central-West, North, and Northeast). One hundred and ten strains were selected for identification using the MALDI-TOF technique. The genera with the most significant spectrum of action were Lactococcus, Lactobacillus, and Pediococcus in the antimicrobial action test against pathogens, concluding that Lactobacillus showed resistance to several antibiotics. The analysis of antimicrobial action made it possible to verify the potential production of antimicrobial compounds by LABs against the primary pathogens of food origin. The most significant reduction in pH could be observed from 24 h to 48 h, ranging from 6.8 (0 h) to 4.74 (48 h) for Lactobacillus and Lactococcus. All isolates survived tolerance tests at pH=3.0 and bile salts (0.5 %), with survival rates ranging from 34.2 to 69.9 % at pH = 3.0 and above 82 % at 0.5 % bile salts. Lacotococcus and Lactobacillus isolates presented the plnEF and plnNC8 genes. This study contributes to the search for alternatives in the treatment of bacterial infections with a reduction in the use of antibiotics, which, due to the increase in bacterial resistance, is causing difficulties in treating diseases caused by these microorganisms. pH is an important parameter when it comes to food safety and conservation. Tolerance to acid stress and bile salts are important properties in evaluating probiotic potential and the ability to maintain high counts under these conditions. The presence of the plnEF and plnNC8 genes suggests bacteriocin production.
Keywords: Biopreservatives; Gastrointestinal tract survival; Lactobacillus spp.; Proteinase k